Apatosaurus - Landau, Elaine (New York : Children's Press, 2007)
Describes the physical characteristics, habits, and natural environment of the huge plant-eating apatosaurus and discusses theories on why it became extinct.
Picture this -- Hey, big guy -- Super tail! -- The life of Apatosaurus -- Feeding time! -- Our changing world.
Includes bibliographical references (p. 44) and index.
4.9
3-6
Keywords: Apatosaurus -- Juvenile literature; Apatosaurus; Dinosaurs; Apatosaurus; Dinosaurs; Apatosaurus; Dinosaurs